Profiles of Proinflammatory Cytokines and T Cells in Patients With Tourette Syndrome: A Meta-Analysis - Li, Ying; Wang, Xiaolin; Yang, Hanxue; Li, Yanlin; Gui, Jingang; Cui, Yonghua (Frontiers in Immunology, 2022)
Background: Tic disorder is a neurodevelopmental disorder characterized by motor and phonic tic symptoms. Tourette syndrome (TS) is a subtype of tic disorder that shows more persistent tic symptoms. The etiological mechanism of TS concerning immune dysfunction remains unclear due to limited evidence, especially for pediatric TS patients. Method: In the present study, a meta-analysis was performed to confirm the identified changes in proinflammatory cytokines and T cells of pediatric TS patients. A total of five databases, including PubMed, Web of Science, PsycINFO, Google Scholar and the China National Knowledge Infrastructure (CNKI), were used for the literature search. The standardized mean difference (SMD) and mean difference (MD) with a 95% confidence interval (CI) were used to present the effect size of each type of proinflammatory cytokine and T cell. Sensitivity analysis, subgroup analysis and meta-regression analysis were used to explore the heterogeneity of the meta-analysis. This meta-analysis was registered in the International Platform of Registered Systematic Review and Meta-analysis Protocols (number: INPLASY2021110079). Results: In the 25 studies included in this meta-analysis, thirteen studies focused on the levels of T cells, and twelve studies focused on the levels of proinflammatory cytokines. Based on the random-effects model, the pooled MDs are -1.45 (95% CI: -3.44, 0.54) for CD3 cells, -4.44 (95% CI: -6.80, -2.08) for CD4 cells, and 1.94 (95% CI: -0.08, 3.97) for CD8 cells. The pooled SMDs are1.36 for IL-6 (95% CI: 0.00, 2.72) and 2.39 for tumor necrosis factor alpha (TNF-α) (95% CI: 0.93, 3.84). Conclusion: We provided evidence of immune dysfunction in pediatric TS patients, with elevated levels of particular proinflammatory cytokines and disproportionate changes in T-cell subpopulations. Small to large effect sizes were identified for increased IL-6 levels as well as a reduced number of T helper cells, while a large effect size was identified for increased TNF-α levels. These results indicate a close association between peripheral immune activation and TS. However, the most direct and meaningful interaction between peripheral immune status and microglial activation in the central nervous system in TS patients requires further exploration.